2021
DOI: 10.3389/fimmu.2021.701951
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Immune-Related Adverse Events Associated With Immune Checkpoint Inhibitors in Lung Cancer

Abstract: Immune checkpoint inhibitors (ICIs) are novel immunotherapy-based drugs that have become increasingly popular in the treatment of lung cancer. Researchers have recognized ocular immune-related adverse events (irAEs) secondary to ICIs because of their vision-threatening characteristics. However, they are incompletely characterized and no studies have reported the ICI-related ocular irAEs in lung cancer. Therefore, we aimed to comprehensively illustrate the clinical characteristics, contributory factors, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 169 publications
(199 reference statements)
0
41
0
Order By: Relevance
“…The relatively rare ophthalmic irAEs have been only reported in less than 5% of patients treated with anti-PD-1 antibody-containing regimens ( 15 ). The optic neuritis was the fifth most common ICI-related ocular adverse event in lung cancer, and most of the patients with ocular irAEs other than ophthalmoplegia could be relieved after drug withdrawal and glucocorticoid treatment ( 17 , 27 ). Optic neuritis is one of the ophthalmic emergencies and may lead to permanent vision damage if left inappropriately treated ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively rare ophthalmic irAEs have been only reported in less than 5% of patients treated with anti-PD-1 antibody-containing regimens ( 15 ). The optic neuritis was the fifth most common ICI-related ocular adverse event in lung cancer, and most of the patients with ocular irAEs other than ophthalmoplegia could be relieved after drug withdrawal and glucocorticoid treatment ( 17 , 27 ). Optic neuritis is one of the ophthalmic emergencies and may lead to permanent vision damage if left inappropriately treated ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review reported that ophthalmoplegia (40.51%), uveitis (20.25%), dry eye (17.72%), retinopathy (5.06%), conjunctivitis (5.06%), and optic neuritis (3.80%) were the most common immune checkpoint inhibitor (ICI)-related ocular adverse events in lung cancer ( 17 ). A recent report showed that pembrolizumab might lead to inflammatory optic neuritis, which could reverse by the cessation of ICI and the use of corticosteroids ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…irAEs of the eye are rare and occur in <1% of patients treated with ICIs ( 212 , 213 ). Uveitis can be a complication of ICI treatment ( 214 ).…”
Section: Clinical Manifestations Of Ici Associated Autoimmunitymentioning
confidence: 99%
“… 2 According to recent literature reviews, ocular irAEs occur in an estimated 1–4% of patients with dry eye disease (1–24%) and uveitis (1%) being most common. 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%